Ta‘ālīm Aḥmad Khatīb al-Sambāsī al-Ṣūfiyyah fī al-Ṭarīqah al-Qādiriyyah wa al-Naqsyabandiyyah: The Sufi Thought of Ahmad Khatib al-Sambasi in Tarekat Qadiriyah wa Naqshabandiyah (TQN) - Arif Afandi Zarkasyi; M. Najib Abdussalam (University of Darussalam Gontor, Indonesia, 2025)
This article explores the Sufi thought of Ahmad Khatib al-Sambasi, an influential 19th-century Nusantara Sufi, and the characteristics of his Tarekat Qadiriyah wa Naqshabandiyah (TQN). Using a qualitative approach and library research methodology, the study analyzes al-Sambasi's works, particularly Fatḥ al-‘Ārifīn, alongside secondary literature on TQN and Sufism. The research employs documentation for data collection and content analysis for interpretation. Findings reveal that al-Sambasi developed a comprehensive spiritual system grounded in tauḥīd and ma‘rifah, featuring systematic dzikr methods and spiritual practices. His teachings successfully integrate Syarī‘ah and Ḥaqīqah, emphasizing a balance between exoteric and esoteric dimensions. The TQN's distinctive features include a hierarchical structure, specific rituals like bai‘at and talqīn dzikr, and strict ethical guidelines for followers. Al-Sambasi's significant contribution lies in adapting classical Sufism to the Nusantara context, fostering widespread acceptance in the region. The study concludes that al-Sambasi's thought offers a balanced and comprehensive spirituality model, relevant both in his time and in contemporary Islamic spirituality.